Creep of concrete during Alkali-Aggregates Reaction. (20th June 2022) - Lacombe, Clément; Vidal, Thierry; Sellier, Alain; Noret, Christine; Anthiniac, Patrice
Abstract: The sustainability of operating hydropower schemes is an important issue in the context of ecologic-transition. However, some concrete dams are affected by Alkali-Aggregates Reaction (AAR), which can be a major concern for their safety. In the case of arch dams, where the overall stability is based on the transmission of stresses from the structure to the foundation, the swelling induced by the reaction can generate additional stresses. As concrete creeps under mechanical loading, a competition occurs between stress rising due to swelling and stress release due to creep. To capture this competition, the creep test must be led after a significant level of swelling and not before its initiation as often observed in lab tests. So, a new testing program has been developed to capture interactions between compressive creep and swelling induced by ongoing AAR. It was applied on two similar concretes differing one-another only by the reactivity of their aggregates. After one month of autogenous curing, concrete samples were immersed in sodium-hydroxide solution to accelerate the AAR. Once a significant part of the maximal free swelling is reached, they were sealed to keep the ongoing reaction, and a part of them were loaded uniaxially, while the others remained free of stress. The results show that 40% of the swelling occurring before the loading was rapidly erased in the compressed direction. Afterwards, similar creep evolutions were observed for reactive and non-reactive concretes, without any report of the swelling in the free directions for the reactive one, despite the ongoing of AAR. Highlights: Uniaxial compressive creep test on concrete after significant AAR free swelling. 40% of the free swelling is resorbed by a loading of 30% of concrete compressive strength. Strains in loaded and free directions measured during long term compressive creep.